1956
DOI: 10.1002/maco.19560071107
|View full text |Cite
|
Sign up to set email alerts
|

Oxydation von Titan

Abstract: Es wird der Versuch unternommen, die von den einzelnen Autoren gefundenen Zeitgesetze zu deuten. Die in den verschiedenen Temperaturbereichen und Oxydationszeiten beobachteten Zeitgesetze stehen in einem sinnvollen Zusammenhang. Unterhalb 300° C, wo das logarithmische Zeitgesetz der Oxydation herrscht, ist eine nennenswerte Sauerstofflöslichkeit im Titan während der Oxydation nicht zu beobachten. Erst oberhalb dieser Temperatur wird die Sauerstoffaufnahme durch Titan beachtlich. In diesem Temperaturbereich wir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1959
1959
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Until now there has been no satisfactory explanation as to why such thick films should obey a cubic oxidation rate law for n-type semiconductors. Kofstad and Hauffe (13) find that a cubic rate law exists also for the oxidation of titanium (TiO.~ also being an n-type semiconductor). They suggest that a cubic rate law could be the result of two factors, namely, the high solubility of oxygen in titanium and the dependence of the value of the diffusion "constant" on the oxygen concentration in titanium.…”
Section: Discussionmentioning
confidence: 99%
“…Until now there has been no satisfactory explanation as to why such thick films should obey a cubic oxidation rate law for n-type semiconductors. Kofstad and Hauffe (13) find that a cubic rate law exists also for the oxidation of titanium (TiO.~ also being an n-type semiconductor). They suggest that a cubic rate law could be the result of two factors, namely, the high solubility of oxygen in titanium and the dependence of the value of the diffusion "constant" on the oxygen concentration in titanium.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of the thin interference color film has been found experimentally to obey a logarithmic growth law (3), and it is probable, therefore, that this is an example of the applicability of Uhlig's thin film growth law to a case of metal oxidation. The initial oxidation of hafnium (34) and titanium (27)(28)(29)(30) has been found also to obey a logarithmic law at temperatures below 350~…”
Section: Discussionmentioning
confidence: 99%
“…At present there is no adequate model to account for cubic oxidation of zirconium, although it has been suggested that such kinetics may be partially due to oxygen solution in the metal (7,18). Consequently, it appears more appropriate, at least for long exposures, to represent the extensive data for the chemically polished specimens from this investigation in terms of a parabolic equation accounting for lattice diffusion of oxygen in the oxide and oxygen solution in the metal.…”
Section: T H E P R E S E N T Studies W E R E C a R R I E D Out To E X...mentioning
confidence: 99%